2016
DOI: 10.7554/elife.16167
|View full text |Cite
|
Sign up to set email alerts
|

A neural basis for the spatial suppression of visual motion perception

Abstract: In theory, sensory perception should be more accurate when more neurons contribute to the representation of a stimulus. However, psychophysical experiments that use larger stimuli to activate larger pools of neurons sometimes report impoverished perceptual performance. To determine the neural mechanisms underlying these paradoxical findings, we trained monkeys to discriminate the direction of motion of visual stimuli that varied in size across trials, while simultaneously recording from populations of motion-s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
54
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(65 citation statements)
references
References 66 publications
(127 reference statements)
10
54
1
Order By: Relevance
“…1 A) gratings and contrast-modulated (second-order; Fig. 1 B) gratings, both of which are known to induce surround suppression [22] , [23] , [24] . Subjects performed a temporal two-alternative forced choice (2AFC) contrast matching task, judging which of two sequentially presented target stimuli had higher contrast.…”
Section: Methodsmentioning
confidence: 99%
“…1 A) gratings and contrast-modulated (second-order; Fig. 1 B) gratings, both of which are known to induce surround suppression [22] , [23] , [24] . Subjects performed a temporal two-alternative forced choice (2AFC) contrast matching task, judging which of two sequentially presented target stimuli had higher contrast.…”
Section: Methodsmentioning
confidence: 99%
“…Contrasting this view, studies in monkeys demonstrate 69 that the strength of neuronal surround suppression in the MT is low and cannot explain the 70 3 reported high level of deterioration in behavioral performance (Liu, et al, 2016). Moreover, many…”
mentioning
confidence: 97%
“…Tadin and colleagues have shown that TMS-induced periods of reduced 66 excitability in MT were associated with weakening of SS, and suggested that such disruptive TMS 67 is interfering with inhibitory processing within MT/V5, which, in turn, improves perception of 68 large moving stimuli (Tadin, et al, 2011). Contrasting this view, studies in monkeys demonstrate 69 that the strength of neuronal surround suppression in the MT is low and cannot explain the 70 3 reported high level of deterioration in behavioral performance (Liu, et al, 2016). Moreover, many…”
mentioning
confidence: 99%
“…A decrease in GABA-mediated inhibition has also been proposed to explain the weaker spatial suppression for motion in schizophrenia . However, pharmacological manipulations to increase the levels of GABA resulted in a decrease of spatial suppression in humans (Michael-Paul Schallmo et al 2018) and did not affect the surround suppression of neurons in the monkey (Liu, Miller, and Pack 2018) linked to the perceptual spatial suppression (Liu, Haefner, and Pack 2016) . Overall, current evidence suggests that a decline in GABAergic function cannot explain the perceptual differences in surround suppression between younger and aged participants, or between healthy controls and patients with schizophrenia.…”
Section: Discussionmentioning
confidence: 99%